Konsep-Konsep Strategi Pembelajaran - Alya Nur Annisha; Miftahul Hasanah; Gusmaneli Gusmaneli (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Learning strategies play a vital role in determining the success of the educational process, particularly in achieving learning objectives effectively and efficiently. This article aims to comprehensively examine fundamental concepts of learning strategies by addressing five main research questions: (1) what is the definition of learning strategies? (2) how are models, approaches, strategies, methods, and techniques of learning interrelated? (3) what are the classifications of learning strategies? (4) what are the essential components of a learning strategy? and (5) what considerations are important in selecting an appropriate learning strategy? Using a descriptive-qualitative approach, this article draws upon various educational literature, both classical and contemporary, to formulate a comprehensive understanding of learning strategies. The discussion on the definition highlights that a strategy is not merely a technical step but also a pedagogical framework that reflects a systematic way of thinking. Furthermore, this article emphasizes the importance of understanding the interconnectedness of learning models (conceptual frameworks), approaches (philosophical orientations), strategies (overall plans), methods (procedural steps), and techniques (practical actions) in order for educators to design cohesive and holistic learning processes. The classification of learning strategies is discussed based on the learning approach used, such as expository, inquiry-based, cooperative, contextual, and problem-based strategies—each with its own advantages and challenges. The article also identifies key components of learning strategies, including learning objectives, student characteristics, materials, media, methods, and evaluation. In choosing the appropriate strategy, the author highlights the need to consider factors such as learning goals, learner characteristics, available resources, and the socio-cultural context of the learning environment, particularly within the framework of Islamic education. The findings of this study are expected to contribute both theoretically and practically to the development of more contextual, adaptive, and relevant learning designs, especially for educators and prospective teachers within Islamic State Universities.